EARLY TEEN EMOTIONAL MANAGEMENT - Hani Aviriani; Khairani Khairani (Universitas Negeri Padang, 2019)
Adolescence is a period where individuals experience a developmental transition from childhood to adulthood, that is capable of mental, emotional, social, and physical maturity Emotions can affect individual ways of thinking and even actions. Inability to manage emotions is a picture of uncontrolled emotions and reflects emotional imbalance. This study aims to describe the emotional management of early adolescents in terms of the ability to control the interpretation of stimuli that cause emotions, and the ability to control the expression of emotions that arise. This research uses a quantitative method with a descriptive approach. The study population was 785 students of SMP N 7 Padang. The sample in this study amounted to 265 people determined by proportional random sampling. The instrument used in this study was a Likert scale model questionnaire. The data obtained were processed using percentage techniques. The findings of this study reveal that the ability to manage students' emotions in controlling the interpretation of stimuli that cause emotions is in the good category with a percentage of 67.5%, and the ability of students to control the expression of emotions that appear is in the good category with a percentage of 70.2%. So the ability to manage the emotions of early teens is classified as good with a percentage of 76.6%.